Role of KNDy neurons in puberty onset in male offspring following prenatal androgen exposure - Runfei Ge; Yun Zhang; Yongting Yuan; Tingting Li; GuiYu Qiu; Shuaijun Guo; Lianguo Fu (Endocrine Connections, 2025)
Objective: Emerging evidence links prenatal androgen excess to altered pubertal timing, yet the neuroendocrine mechanisms mediating this effect in male offspring remain poorly characterized. This study aimed to investigate the effects of prenatal androgen exposure on the timing of puberty onset in male offspring and the role of KNDy neurons in this process. Methods: Eight-week-old pregnant Sprague–Dawley rats (n = 16) were randomized into control (olive oil) and prenatal androgen (PNA, testosterone injection) groups (n = 8 per group). Hypothalamic samples of six male offspring rats at postnatal day (PND) 21 (n = 3 per group) were collected for transcriptome analysis. The time of puberty onset was recorded in 36 male offspring (n = 18 per group). Serum samples and hypothalamic tissue from 12 male offspring rats (n = 6 per group) were collected, and GnRH, LH, FSH, and kisspeptin 1 protein levels were measured by ELISA. The mRNA levels of Kiss1, Tac3, and Pdyn were measured by real-time qPCR. In the brains of six male offspring rats (n = 3 per group), protein levels of kisspeptin, neurokinin B (NKB), and dynorphin (Dyn) in the arcuate nucleus (ARC) were measured using immunohistochemistry. Results: Compared to controls, PNA male offspring rats showed significantly earlier puberty onset (P < 0.001). At PND21, Tac3 (P < 0.01) and Pdyn (P < 0.05) expression levels increased significantly in PNA male offspring rats. At puberty, ARC kisspeptin protein levels increased (P < 0.01), while dynorphin protein levels decreased (P < 0.01) in PNA male offspring rats. Conclusion: Prenatal androgen exposure accelerates puberty onset in male offspring rats, likely by activating Tac3 expression in early life and reducing ARC dynorphin inhibition of kisspeptin neurons at puberty.